2014
DOI: 10.1186/1746-6148-10-60
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of dietary fish oil with plant oils is associated with shortened mid intestinal folds in Atlantic salmon (Salmo salar)

Abstract: BackgroundFish meal and fish oil are increasingly replaced by ingredients from terrestrial sources in the feeds for farmed salmonids due to expanding production and reduced availability of marine feed raw material. Fish oil that is rich in n-3 polyunsaturated fatty acids is considered beneficial to human health in general and to prevent intestinal inflammation and carcinogenesis in particular. In contrast, n-6 fatty acids that are present in many vegetable oils have been associated with increased risk of colit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 47 publications
0
33
0
Order By: Relevance
“…In the present study, the mRNA levels of tgfb and il17d of the algal groups were similar to those of the control fish. The transcripts of il1b and tnfa were not altered in the intestine of Atlantic salmon fed olive oil, rapeseed oil or soybean oil (Moldal et al, 2014). However, soybean oil feeding was found to lower the igm and igt levels in the distal intestine of the fish (Moldal et al, 2014).…”
Section: Health Status Upon Feeding Desmodesmus To Atlantic Salmonmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the mRNA levels of tgfb and il17d of the algal groups were similar to those of the control fish. The transcripts of il1b and tnfa were not altered in the intestine of Atlantic salmon fed olive oil, rapeseed oil or soybean oil (Moldal et al, 2014). However, soybean oil feeding was found to lower the igm and igt levels in the distal intestine of the fish (Moldal et al, 2014).…”
Section: Health Status Upon Feeding Desmodesmus To Atlantic Salmonmentioning
confidence: 99%
“…The transcripts of il1b and tnfa were not altered in the intestine of Atlantic salmon fed olive oil, rapeseed oil or soybean oil (Moldal et al, 2014). However, soybean oil feeding was found to lower the igm and igt levels in the distal intestine of the fish (Moldal et al, 2014). The feeding of the algal biomass in this study did not alter the level of igt in the distal intestine of Atlantic salmon.…”
Section: Health Status Upon Feeding Desmodesmus To Atlantic Salmonmentioning
confidence: 99%
“…Intestinal folds and tunica mucosa contain connective tissue and blood vessels involving in nutritional absorption and immunological processes (Eurell & Frappier, 2006). Shortened intestinal folds might be associated with reduced intestinal surface and impaired nutrient absorption and growth, but previous reports have suggested that partial substitution of dietary fish oil with vegetable oils does not have any major negative impact on intestinal health of Atlantic salmon (Moldal et al, 2014). Tunica mucosa in CO group was thicker than FO group, nevertheless height and diameter of intestinal folds also increased predominantly in LO group.…”
Section: Discussionmentioning
confidence: 73%
“…Changes in dietary FA composition have been reported to affect FA composition of fish lipids storage and cell membranes in hepatic (Kjaer et al, 2008;Fountoulaki, Alexis, Nengas, & Venou, 2005;Castro et al, 2015), intestinal (Caballero et al, 2003;Ruyter, Moya-Falcón, Rosenlund, & Vegusdal, 2006) and digestive tract tissues (Olsen, Myklebust, Kaino, & Ringo, 1999;Moldal et al, 2014 of alpha-linolenic acid, accumulations of fat droplets in enterocytes of pyloric appendages and midgut were observed previously (Olsen, Myklebust, Ringo, & Mayhew, 2000). These changes in alimentary tract can accommodate transport and metabolism of fat in the body and decrease protein and fat digestion (Francis, Turchini, Jones, & De Silva, 2007).…”
Section: Introductionmentioning
confidence: 67%
“…trypsin inhibitors, saponins) present in plant-based feeds (Knudsen et al, 2008). In the study published for S. salar, Moldal et al (2014) identified moderate alterations in the mRNA transcript levels of selected immune-related genes (e.g. CD3ζ, MHC class II) between all groups fed vegetable oils compared to the group fed fish oil.…”
Section: R Panicz Et Almentioning
confidence: 96%